PENGARUH PERSEDIAAN BERAS, PRODUKSI BERAS, DAN HARGA BERAS TERHADAP KETAHANAN PANGAN KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2008-2010 - Jasa Wijaya Karya (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
The threat of food crisis hit Indonesia. Various responses point out that this conditionoccurs because of the ability to produce rice decreased while the amount of rice consumption continues to grow in line with population growth. This situation is exacerbated by the high food prices are causing more and more limited access to food. Central Java Province as one of the largest rice producer in Indonesia has a responsibility to meet the demands of rice consumption. Therefore, the preparation of this study has the objective to analyze the state of food security in Central Java with a focus on the availability of rice at each district / city in Central Java province.Keyword: Availability Ratio, Inventories Rice, Rice Price, Rice Production